Unemployment Duration of First Time Job Seekers: A Case Study of Bahawalpur - Khan, Tasnim; Yousaf, Fatima (Asian Journal of Economic Modelling, 2013)
Educated youth unemployment is crucial issue for developing countries. The social and economic costs of unemployment at individual, household and national level are universal. But there are few studies on unemployment duration when the individuals start jobs and its determinants in developing countries. We have analyzed the determinants of unemployment for first time jobs seekers, taking primary data of all employed or self- employed individuals between the age group of 20-35 years. The dependent variable is duration of unemployment, which a person has to suffer after obtaining last degree of education, before leaving unemployment to employment. Professional and general education levels, training, age, salary, gender preference for public / private sector job, marital status has been taken as independent variables. Our findings are that professional degree holders suffer greater unemployment duration, but in case of general education, higher education degree holders suffer less unemployment duration than their counterpart of low degree holders. Training, marital status, high salary, head of household and household size reduce the duration of unemployment, but the stated preference for government job increases the duration of unemployment.